A taxonomic revision of the Capparis spinosa group (Capparaceae) from the Mediterranean to Central Asia - Fici, Silvio (Phytotaxa, 2014)
A revision of the Capparis spinosa group has been carried out in southern Europe, northern Africa, western and central Asia, in order to provide a uniform taxonomic treatment of its representatives. The xerotropical origin of this group, showing disjunct distribution in several holoarctic and paleotropical regions, is underlined and the different species concepts historically adopted are discussed. In the present treatment a single species is recognized, C. spinosa, represented in the study area by two subspecies. C. spinosa subsp. spinosa shows derived characters, high polymorphism and a wide distribution range from the Mediterranean eastwards to China and Nepal. C. spinosa subsp. rupestris, less variable and showing phenotypic characters closer to the tropical stock of the group, is recorded in the Mediterranean Region and the Sahara. On the basis of herbarium and field investigations, the variability and distribution of the two subspecies are examined. Within each subspecies some varieties are recognized, for which morphological, chorological and autecological data are presented. Four new combinations (C. spinosa subsp. spinosa var. herbacea, C. spinosa subsp. spinosa var. atlantica, C. spinosa subsp. rupestris var. ovata, C. spinosa subsp. rupestris var. myrtifolia) are proposed.